Benefits of Adolescent Women's Reproductive Health Records as a Basis for Screening Preconception Care: A Research and Development Study - Fibrila, Firda; Sulistyowati, Sri; Akhyar, Muhammad; L, Anik (KnE Social Sciences, 2023)
The health status of women is one of the factors that can affect the status of pregnancy. To avoid risky pregnancies and produce healthy babies, it is very important for a woman to take care of her reproductive health. One of the efforts is to conduct early detection on a regular basis starting from the age of teenagers. This developmental research was carried out using the Four-D model, to obtain a simple early detection medium in preconception care. Sixty selected young women participated in a limited trial. Respondents who participate in a limited-scale trial will go through 3 stages. The data obtained were analyzed descriptively. The success of using the application as a function of simple screening media for preconception care reached 96.67%. It was identified that 57% of adolescent girls were detected to have health problems such as poor nutritional status and anemia. A total of 71.7% stated that this application applies very well on adolescent girls in order to keep them healthy as an initial step in preparation for pregnancy. As many as 73.3% of respondents stated that the developed application provided new knowledge related to preconception preparation. There is strong evidence that the resulting media performs well as a simple early detection tool for preconception care. Therefore, it needs to be refined to provide more optimal results. Keywords: screening, preconception, adolescent